2011
DOI: 10.1289/ehp.1002267
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Assessment in Cohort Studies of Childhood Asthma

Abstract: BackgroundThe environment is suspected to play an important role in the development of childhood asthma. Cohort studies are a powerful observational design for studying exposure–response relationships, but their power depends in part upon the accuracy of the exposure assessment.ObjectiveThe purpose of this paper is to summarize and discuss issues that make accurate exposure assessment a challenge and to suggest strategies for improving exposure assessment in longitudinal cohort studies of childhood asthma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 100 publications
0
19
0
Order By: Relevance
“…Overall, the mean rarefied Chao1 score for species richness was 12.0 (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The mean Shannon diversity index was 1.38, ranging from 0.17 to 2.36 (Table 4).…”
Section: Richness and Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the mean rarefied Chao1 score for species richness was 12.0 (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The mean Shannon diversity index was 1.38, ranging from 0.17 to 2.36 (Table 4).…”
Section: Richness and Diversitymentioning
confidence: 99%
“…19 Thus, the gut microbiota is essential to human health, yet the acquisition and development of this microbial community during infancy remains poorly understood. 3 In the current study, we address this gap in knowledge using new sequencing technology and detailed exposure assessments 20 of healthy Can adian infants selected from a national birth cohort to provide representative, comprehensive profiles of gut microbiota according to mode of delivery and infant diet. 21 We used quantitative polymerase chain reaction as described by Penders and colleagues 5 for targeted analysis of Clostridium difficile because of the organism's association with atopic allergic disease in a previous study.…”
mentioning
confidence: 99%
“…An accurate method for estimating environmental exposure to airborne contaminants is essential to understanding both the environment and possible links to respiratory health problems. Until now characterizing children's exposures has relied primarily on measurements of settled dust or general area stationary indoor monitors (SIM) [2]. While some studies have found a significant association between concentrations of indoor particulate matter (PM) and respiratory morbidity, others have not [3-7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews have highlighted the need for improved exposure assessment methods in epidemiological studies 5 12. Although ideally one would monitor personal exposure throughout life, this is clearly not feasible and alternative methods of assigning an index of exposure have been used, for example, central outdoor monitors, land use regression (LUR) models or temporary indoor static monitors.…”
Section: Introductionmentioning
confidence: 99%